211k views
1 vote
Please someone solve this equation for me i only have 2 mins

Please someone solve this equation for me i only have 2 mins-example-1
User Layla
by
4.8k points

2 Answers

3 votes

Answer:

s = 6

Explanation:

Given: -2s + 8(9 - s) = 3 - (9 - 3s)

Get rid of the brackets by using the distributive property:

-2s + 72 - 8s = 3 - 9 + 3s

You can rearrange the items so the expression is easier to solve:

-2s - 8s + 72 = 3s + 3 - 9

Combine like terms:

-10s + 72 = 3s - 6

Now let's subtract 72 from both sides of the expression:

-10s = 3s - 78

Next, subtract 3s from both sides of the expression:

-13s = -78

Lastly, divide each side of the expression by -13 to get:

s = 6

Hope this helped!

User Ian Hatch
by
5.0k points
0 votes

Answer:

s=6

Explanation:

User Pavel Sharanda
by
5.7k points